The role of dispositional emotion regulation strategies on the longitudinal emotional process and subjective performance during a competitive season - Cece, V.; Guillet-Descas, E.; Brenas, M.; Martinent, G. (European Journal of Sport Science, 2021)
The purpose of this study was to shed light on the associations between emotion regulation (ER) strategies used, their emotional processes (including cognitive appraisals and discrete emotions), and subjective performance across a competitive season. A sample of fifteen national-level rink hockey players completed ER questionnaire at the beginning of the season (T0) and reported their experiences of everyday appraisal, emotions, and subjective performance every week. A series of hierarchical linear modelling analyses (HLM) were performed to investigate the associations between the variables. Sobel tests were computed to identify the mediating effects of emotions and appraisals on these relationships. HLM results revealed that (a) T0 adaptive ER strategies were positively related to adaptive appraisals; (b) adaptive appraisals were positively related to pleasant emotions and negatively with unpleasant emotions and opposite relationships emerged for maladaptive appraisals; (c) happiness was positively associated with subjective performance. Sobel tests provided evidence of mediating effects of (a) appraisals in the relationships between T0 adaptive ER and pleasant emotions; and (b) happiness in the relationships between appraisals and subjective performance. The results highlighted the positive relationships between the adaptive dispositional ER strategies at the beginning of the season and the emotional experiences. Moreover, the analyses revealed relationships between appraisals, emotions, and subjective performance of athletes. In sum, this study provided additional knowledge about the capture of the emotional process during a competitive season highlighting the associations between a variety of emotions and selected key variables in a competitive context (i.e. ER strategies, appraisal, subjective performance).